The integration of the elastic surface of a circular plate with any system of radially symmetric loads and supports - Almazan, Anselmo D. (1972)
The problem presented in this thesis deals with the integration of the elastic surface of a circular plate with any system of radially symmetric loads and supports. The equilibrium equation defining the elastic state of the circular plate is considered with the load function expressed in terms of the unit step function, the unit impulse and the unit doublet. The general solution to this equilibrium equation expressed in terms of the unit step function is obtained by the application of the Laplace Transform method of analysis. This general solution is used in the analysis of circular plate with or without hole in the center under various edge conditions and any number of internal supports.
Thesis (M. S.)--University of the Philippines.
Keywords: Plates (Engineering).; Elastic plates and shells